Ferrimagnetism in two antiferromagnetic transverse Ising thin films. (1st February 2017) - Kaneyoshi, T.
ABSTRACT: The phase diagrams and temperature dependences of total magnetization m T in two antiferromagnetic transverse Ising thin films with same thickness L ( L = 4), consisting of two (A and B) layers, are studied by the uses of the effective-field theory with correlations and the mean-field theory. The A and B layers are consisted of spin-1/2 atoms and they have opposite spin directions. Two magnetic structures are discussed and they exhibit rather different and characteristic behaviors for the magnetic properties. Many characteristic behaviors observed in standard ferrimagnetic materials as well as novel phenomena have been obtained for the thermal variations of m T in the both systems, when the crystallographically equivalent conditions between the A and B layers are broken.